Valuing visitors willingness to pay to generate revenues for managing Putrajaya Botanical Garden - Abdul Aziz, Izza Shazleen; Kozlowski, Marek; Othman, Mohd Shahwahid (Penerbitan Akademia Baru, 2019)
Policymakers and recreation site managers use changes in fee structure, either introducing park entrance fees or increasing existing ones, to generate revenues, improve services, and reduce damages associated with visitor’s overuse. The sudden increase in park usage fee, however, can make the park inaccessible to certain segments of visitors. Understanding park users' response to changes in fees and its implication on park use equity is, thus, important to achieving a park's full potential in a socially and environmentally responsible way. This information is crucial especially for developing countries, where the issue has received relatively less attention and underfunded. This paper contributes to the literature on park access fees by empirically assessing park use equity between and among international and local visitors visiting Putrajaya Botanical Garden, Malaysia and developing an approach for determining predictors and mean willingness to pay values for park entrance. Results of our survey-based approach show a positive willingness to pay values for park entrance and fee increases. Our results also show that it is possible to raise revenue without exacerbating existing park use differences.